SUSTAINABLE LOCAL DEVELOPMENT: ESSENCE AND CONTENT - Zhydkov , K. S. (Theory and Practice of Public Administration, 2021)
Sustainable local development is a holistic approach that integrates social, environmental and economic considerations into the processes and actions of local communities on their path to sustainable development. This entails progress in all forms of community joint capital: natural, physical, economic, human, social and cultural. Despite the lack of a definitive consensus, sustainable local development, like sustainable development, has three main elements that researchers and practical workers generally agree on: the environment (biosphere and resource management), society (equity, integration, cohesion and poverty) and economics (qualitative and quantitative economic indicators). Accordingly, several theories and factors that have influenced and / or are influencing sustainable local development over time can be identified: environmental modernization, weak and strong sustainability; social economy, economic development of communities, green economy and self-sufficiency; resource efficiency, cyclical economy and urban metabolism; “social” and “fair” aspects of sustainability; stability; environmental footprint, the concept of public health. The main conclusion that emerges from the current study to assess the effectiveness of sustainable local development is that this area is not yet fully developed. Despite the fact that there are many techniques, their development seems to be unsystematic, without a trace. Most of these techniques, as well as the resulting decision-making processes, do not recognize the importance of several aspects of sustainability: systemic areas; the urgent need to integrate the interests of human health and the environment; the existence of a “globalized world” in which resources are produced and consumed in different regions; the need to focus on social integration, justice, community mobilization and security. Taking these aspects into account requires finding a common language between researchers and practical workers on sustainability and with those who shape the relevant public policy.